Como usar a tecnologia móvel para promover o acesso aberto: o caso da biblioteca da ESTeSL - Carvalho, Paula Seguro de (Cadernos BAD, 2014)
Como usar a tecnologia móvel para promover o acesso aberto: o caso da biblioteca da ESTeSL